Sequence-specific, mechanophore-free mechanochemistry of DNA - Hahmann, Johannes; Schüpp, Boris; Ishaqat, Aman; Selvakumar, Arjuna; Göstl, Robert; Gräter, Frauke; Herrmann, Andreas (Chem, 2025)
Nucleic acids, such as DNA, are integral components of biological systems in that they steer many cellular processes and biotechnological applications. In addition, their monomer-precise sequence and accurately predictable structure render them an excellent model for exploring fundamental problems in nanotechnology and polymer science. In the field of polymer mechanochemistry, predetermined breaking points, called mechanophores, are used to endow macromolecules with chain-scission selectivity when subjected to external forces. However, this approach entails cumbersome chemical synthesis and limited outcome analysis. Here, we show the mechanophore-free, near-nucleotide-precise scission of nicked double-stranded DNA in a combined experimental and computational approach. We leverage next-generation sequencing to achieve monomer-level precision in assessing chain scission. Additionally, we monitor and control the scission distribution on the polymer’s backbone. Our research highlights the potential of DNA as a model polymer in the field of polymer mechanochemistry.
Online verfügbar: 2. Januar 2025, Artikelversion: 10. April 2025
Gesehen am 06.10.2025